Use of nylon-cotton columns for the purification of Toxoplasma gondii - Takeda Kiyomi, Augusta (1969)
A simple procedure for purification of toxoplasma from mouse peritoneal exudate in columns of nylon-cotton is described, showing reproductibility and satisfactory recovering of the parasites.